Ellsberg meets Keynes at an urn - Soo-Hong Chew; Bin Miao; Songfa Zhong (Quantitative Economics, 2023)
Keynes (1921) and Ellsberg (1961) have articulated an aversion toward betting on an urn containing balls of two colors of unknown proportion to one with a 50-50 composition. Keynes views this as reflecting different preferences for bets arising from different sources of uncertainty. Ellsberg describes this as weighting the priors arising from the unknown urn pessimistically. In two experiments, we observe substantial links between attitude toward almost-objective uncertainty and attitudes toward multiple-prior uncertainties in terms of ambiguity and its corresponding compound risk. Our findings point to a shared component across domains of uncertainty and motivate the need for further theoretical development.
Keywords: C91; D81; 330; Ambiguity; source preference; maxmin expected utility; recursive utility; experiment